Serum uric acid levels in borderline personality disorder and its relationship with impulsivity - Kilicaslan, Asli Kazgan; Yildiz, Sevler; Kurt, Osman; Korkmaz, Sevda (Cukurova Univ, Fac Medicine, 2021)
Purpose: The aim of this study is to investigate the serum uric acid levels in patients diagnosed with borderline personality disorder (BPD) who do not use drugs and explore their possible relationship with impulsivity. Materials and Methods: Sixty-nine patients diagnosed with BPD and 54 healthy controls were enrolled in this study. All participants were administered a sociodemographic data form and the Barratt Impulsivity Scale Short Form (BIS-11). Subsequently, fasting venous blood samples were collected from all participants and serum uric acid levels were studied. Results: It was found that serum uric acid levels, BDI-11 subdimension and total scores, and the BDI total score were significantly higher in patients diagnosed with BPD than in the control group. A significant positive correlation was seen between serum uric acid levels and the BDI-11 scale score. Conclusion: This study report higher serum uric acid levels in patients diagnosed with borderline personality disorder who do not use drugs compared to the control group. The results of this study may provide an example that impulsivity in patients diagnosed with borderline personality disorder has a biological basis. Future longitudinal and experimental studies of uric acid levels in BPD patients will allow us an alternative way to diagnose and treat impulsivity in these patients.
Keywords: Borderline personality disorder; impulsivity; uric acid